2013
DOI: 10.1007/s10592-013-0467-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and morphological evidence of hybridization between native Ruditapes philippinarum and the introduced Ruditapes form in Japan

Abstract: Marine aquaculture and stock enhancement are major causes of the introduction of alien species. A good example of such an introduction is the Japanese shortneck clam Ruditapes philippinarum, one of the most important fishery resources in the world. To meet the domestic shortage of R. philippinarum caused by depleted catches, clams were imported to Japan from China and the Korean peninsula. The imported clam is an alien species that has a very similar morphology, and was misidentified as R. philippinarum (herea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 54 publications
2
28
0
Order By: Relevance
“…Hurtado et al (2011) demonstrated that those 2 species (R. decussatus and R. philippinarum) can hybridize, and they found genetic and cytological evidence of the occurrence of hybridization between female R. decussatus and male R. philippinarum using 16S mitochondrial rDNA, ITS2, and 5SrDNA genes. Kitada et al (2013) also demonstrated hybrids of R. philippinarum and other Ruditapes forms. It is believed that hybrid swarms are a virtually intractable problem and that rapid detection of hybridization and response is critical.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Hurtado et al (2011) demonstrated that those 2 species (R. decussatus and R. philippinarum) can hybridize, and they found genetic and cytological evidence of the occurrence of hybridization between female R. decussatus and male R. philippinarum using 16S mitochondrial rDNA, ITS2, and 5SrDNA genes. Kitada et al (2013) also demonstrated hybrids of R. philippinarum and other Ruditapes forms. It is believed that hybrid swarms are a virtually intractable problem and that rapid detection of hybridization and response is critical.…”
Section: Discussionmentioning
confidence: 93%
“…have doubly uniparental inheritance (DUI) of mitochondrial DNA (mtDNA) and 2 different sex-related M-and F-type mtDNAs (Plazzi & Passamonti 2010 and references therein). These authors, and also Kitada et al (2013), recommended that DNA should be obtained from the foot or the adductor muscle, as DUI species carry very little M-type mtDNA in those tissues. We therefore used adductor muscle tissue for DNA extractions in adult individuals.…”
Section: Morphology-based Species Identificationmentioning
confidence: 99%
“…There are various kinds of interactions between invaders and native species, including competition for resources, predation, release of toxins, disease transmission, ecosystem engineering, and hybridization between alien and native species (Hurtado et al 2011). In particular, R. philippinarum is prone to hybridize with native congeneric species (Kitada et al 2013). Hybrids between the allochthonous R. philippinarum and the autochthonous R. decussatus have been found in the north west and north of Spain (Hurtado et al 2011, Habtemariam et al 2015.…”
Section: Differentiation: R Philippinarum and R Decussatusmentioning
confidence: 99%
“…Restocking without considering wild population structure can have potentially disastrous effects on local populations. For example, the intentional stocking of the Japanese shortneck clam from China and the Korean peninsula to enhance depleted Japanese populations backfired when it turned out to be a cryptic species that is now rapidly hybridizing with the native population such that the hybrid proportion now exceeds 50% (Kitada et al 2013).…”
Section: Spatial Planning and Restorationmentioning
confidence: 99%